2015
DOI: 10.12973/eurasia.2015.1393a
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Pre-service Mathematics Teachers’ Beliefs about Mathematics, Mathematics Teaching, and Use of Technology in China

Abstract: This paper investigated pre-service mathematics teachers' mathematics beliefs, beliefs about information and communication technology (ICT), and their relationships. 787 pre-service mathematics teachers in China completed a survey questionnaire measuring their beliefs about the nature of mathematics, beliefs about mathematics learning and teaching, attitudes toward ICT, and beliefs about ICT use in mathematics education. Descriptive statistics, simple correlation analysis, and step-wise progression analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(103 reference statements)
1
12
0
1
Order By: Relevance
“…Authors are not only creating but also adopting, from others, definitions that are not useful from a practical perspective. For example, Thompson’s [2] definition of conceptions, discussed above, has been frequently adopted by a number of authors over a long period—in 2015 alone it was quoted by Yang and Leu [59], Rolka and Roesken-Winter [93], and Sumpter [58] among others. Similarly, Schoenfeld [24] broad definition “beliefs are one’s mathematical worldview, the perspective one takes to approach mathematics and mathematics tasks”, has been adopted in the last few years by several researchers including Tsiapou [94], Jackson [95], and Bofah [60] to frame their studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors are not only creating but also adopting, from others, definitions that are not useful from a practical perspective. For example, Thompson’s [2] definition of conceptions, discussed above, has been frequently adopted by a number of authors over a long period—in 2015 alone it was quoted by Yang and Leu [59], Rolka and Roesken-Winter [93], and Sumpter [58] among others. Similarly, Schoenfeld [24] broad definition “beliefs are one’s mathematical worldview, the perspective one takes to approach mathematics and mathematics tasks”, has been adopted in the last few years by several researchers including Tsiapou [94], Jackson [95], and Bofah [60] to frame their studies.…”
Section: Resultsmentioning
confidence: 99%
“…(data retrieved October 1 st , 2019). Most recent papers as De Corte [9], Sumpter [58], Yang [59], Bofah [60], Ren [61], Hannula [5], and Diego-Mantecón [62] were also selected to cover latest research, although they do not obviously count with so many citations. To avoid sampling bias, chapters from well-known books in the field of mathematics-related beliefs, such as Leder [63], Pepin [64] or Hannula [11] were also examined.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, one of the research participants in a study by Drijvers et al (2015) stated that "the calculators are mainly needed for performing an algorithm or computing an approximate value, and it seems to be a kind of mechanical use of a calculator" (p. 76). It is a practice tool for many students while using technology during the learning of mathematics (Yang & Leung, 2015). MS Excel spreadsheet is especially useful in exploring mathematical concepts, including "numerical and graphical methods to solve problems" (Drier, 2001, p. 170).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…There is skepticism around how technology, such as calculators and computers, help students in Responses making the meaning of mathematical process and how to achieve such a goal to develop conceptual understanding, although it may support in visualization and concretization of many mathematical concepts (Utterberg & Lundin, 2017). Technological tools may not be effective for students to learn some content, such as algebra, because of the requirement of mental and operational manipulation by the learners (Yang & Leung, 2015). Some technological tools, such as multimedia technology, helps students make a connection between the contents they already knew to the new contents, thus facilitating their learning (Marshall, 2002).…”
Section: Figure 5 Percent Of Students Who Believe the Use Of Technolmentioning
confidence: 99%
“…Several international studies have shown that teachers' attitudes towards the potentials of ICT for teaching and learning are a relevant factor for the implementation and/or use of ICT for teaching (Aesaert et al 2015; Ainley 2018; Buabend-Andoh 2012; Drossel et al 2016;Hatlevik and Hatlevik 2018;Petko et al 2018;Tomczyk et al 2015;Tondeur et al 2017;Yang and Leung 2015). Especially for Germany there are many indications of the importance of teachers' attitudes and beliefs with regard to ICT in teaching and learning.…”
Section: Attitudes Of Teachers Towards the Potentials Of Ict For Teacmentioning
confidence: 99%